Using climbing to quantify motor asymmetry in children with cerebral palsy: a pilot study - Monoli, Cecilia; Simoni, Greta; Galli, Manuela; Colombo, Alessandro (Frontiers in Sports and Active Living, 2025)
IntroductionAdapted sports complement traditional rehabilitation for children with cerebral palsy (CP), who require continuous intervention to maintain motor function. This pilot study investigates the feasibility of using a climbing game combined with force sensors to quantify motor asymmetries in children with hemiplegic CP.MethodsEight children with hemiplegic CP participated in climbing games for three consecutive days. Force sensors embedded in the holds measured reaction forces, while marker-less motion capture linked these forces to specific limbs. Two indices, maximum force (Fmax) and mean force (Fmean), were calculated for each limb as potential proxyes for motor asymmetry. Statistical analysis using repeated measures ANOVA assessed the ability of these indices to differentiate between the more and less affected limbs.ResultsThe maximum force index (Fmaxarm) successfully identified significant differences between the more affected and less affected arms in all activities (p≤0.023), with stronger results during structured tasks (p=0.002). However, neither the maximum nor the mean force indices demonstrated significant discriminatory power for the legs, likely reflecting compensatory strategies or reduced asymmetry in the lower limbs.DiscussionThis pilot study supports the potential of Fmaxarm as a robust index to quantify upper limb motor asymmetry. Such an index could be used by therapists to track the evolution of a child’s motor abilities through a game, rather than through less pleasant clinical evaluations. The findings highlight the need for further research to validate these indices in larger cohorts, investigate their longitudinal evolution during rehabilitation, and explore correlations with clinical motor assessments.ConclusionThe results confirm the feasibility of using climbing-based force indices to detect motor asymmetries in children with hemiplegic CP. Future studies could leverage this methodology to provide quantitative feedback on the efficacy of rehabilitation interventions, fostering personalized and engaging therapeutic approaches.